Reflective Case Study on End of Life Care in Post Anaesthesia. Issue 11 (November 2014) - Wade, T
Operating department practitioners (ODPs) are well known for their technical abilities within the perioperative environment and are passionate about the care they deliver. This article will critically reflect on the post anaesthetic care of a dying patient, the challenges of having relatives present, the importance of having a good student/mentor relationship, and will show that student ODPs can deliver compassionate and personalised care.